MONITORAMENTO DOS INDICADORES DE HANSENÍASE EM PERNAMBUCO, 2019 - FABIANO, Beatriz de Oliveira; CRUZ, Renata Rosal Lopes da; LIRA, Monique Léia Aragão de; MORAIS, Ivaneide Izidio de; GOMES, Marília Barros; LIMA, Bruna Rafaela Ferreira da Silva; SANTANA, Priscila Cardoso de; LÓCIO, Maria do Carmo (Hansenologia Internationalis: hanseníase e outras doenças infecciosas, 2019)
.